A single 1-h bout of evening exercise increases basal FFA flux without affecting VLDL-triglyceride and VLDL-apolipoprotein B-100 kinetics in untrained lean men - Magkos, Faidon; Patterson, Bruce W; Mohammed, B. Selma; Mittendorfer, Bettina (American journal of physiology: endocrinology and metabolism, 2007)
1 Washington University School of Medicine, St. Louis, Missouri; 2 Department of Nutrition and Dietetics, Harokopio University, Athens, Greece Submitted 22 November 2006 ; accepted in final form 29 January 2007 Our group (Magkos F, Wright DC, Patterson BW, Mohammed BS, Mittendorfer B, Am J Physiol Endocrinol Metab 290: E355E362, 2006) has recently demonstrated that a single, prolonged bout of moderate-intensity cycling (2 h at 60% of peak oxygen consumption) in the evening increases basal whole-body free fatty acid (FFA) flux and fat oxidation, decreases hepatic VLDL-apolipoprotein B-100 (apoB-100) secretion, and enhances removal efficiency of VLDL-triglyceride (TG) from the circulation the following day in untrained, healthy, lean men. In the present study, we investigated the effect of a single, shorter-duration bout of the same exercise (1 h cycling at 60% of peak oxygen consumption) on basal FFA, VLDL-TG, and VLDL-apoB-100 kinetics in seven untrained, healthy, lean men by using stable isotope-labeled tracer techniques. Basal FFA rate of appearance in plasma and plasma FFA concentration were 55% greater ( P < 0.05) the morning after exercise than rest, whereas resting metabolic rate and whole-body substrate oxidation rates were not different after rest and exercise. Exercise had no effect on plasma VLDL-TG and VLDL-apoB-100 concentrations, hepatic VLDL-TG and VLDL-apoB-100 secretion rates, and VLDL-TG and VLDL-apoB-100 plasma clearance rates (all P > 0.05). We conclude that in untrained, healthy, lean men 1 ) the exercise-induced changes in basal whole-body fat oxidation, VLDL-TG, and VLDL-apoB-100 metabolism during the late phase of recovery from exercise are related to the duration of the exercise bout; 2 ) single sessions of typical recreational activities appear to have little effect on basal, fasting plasma TG homeostasis; and 3 ) there is a dissociation between systemic FFA availability and VLDL-TG and VLDL-apoB-100 secretion by the liver. hepatic lipid metabolism; lipoprotein; stable isotope; tracer Address for reprint requests and other correspondence: B. Mittendorfer, Washington Univ. School of Medicine, Division of Geriatrics and Nutritional Science, 660 South Euclid Ave.; Campus Box 8031, St. Louis, MO 63110 (e-mail: mittendbatwustl.edu )